FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN ASI EKSKLUSIF DI KLINIK PRATAMA SUNGGAL MEDAN TAHUN 2019 - Parida Hanum; Rotua Lenawati Tindaon (Jurnal Maternitas Kebidanan, 2019)
Exclusive breastfeeding is that babies are only given breast milk for 6 months, without the addition of other liquids such as formula milk, oranges, honey, tea water, water, and without additional solid foods such as bananas, milk porridge, biscuits, rice porridge, rice team. The objective of the research was to find factors related to exclusive breastfeeding. The research is done by using cross sectional with Rank Spearman’s test. The population in this study were mothers who had babies 0-6 months in the Klinik Pratama Sunggal in 2019 totaling 15 people and the sampling technique was total Sampling. The result of the research showed knowledgeable mothers (46.7%), higher education (80%), unemployed (60%), supportive (86.7%), not exclusive breastfeeding (80%). The results of the bivariate analysis showed a relationship between maternal knowledge and exclusive breastfeeding (p-value = 0.027), no relationship between maternal education and exclusive breastfeeding (p-value = 0.369), a relationship between maternal work and exclusive breastfeeding (p -value = 0.015), there is no relationship between husband's support and exclusive breastfeeding (p-value = 0.484. The conclusion of this study is that there is a relationship between knowledge and employment with exclusive breastfeeding, there is no relationship between husband's education and support with exclusive breastfeeding. Suggestions for health workers in Medan Sunggal Pratama Clinic in 2019 are expected to improve the quality of services and counseling about exclusive breastfeeding to mothers during pregnancy in order to achieve exclusive breastfeeding for infants.